Development and characterization of a scalable calcium imaging assay using human iPSC-derived neurons - Haustein, Martin Dietrich; Deymier, Caroline; Schlienger, Simon; Lexcellent-Bissler, Laurane; Mawet, Jacques; Gutknecht, Eric; Thenoz, Laure; Brazauskas, Pijus; Renault, Bérengère; Brun, Stéphanie; Winistörfer, Simone; Portmann, Thomas (Frontiers in Cellular Neuroscience, 2025)
Neuroscience drug discovery is challenged by the brain’s structural and cell-type complexity, which is difficult to model in cellular systems compatible with high-throughput screening methods. Calcium oscillation assays, that harness neurons’ intrinsic capability to develop functional neural networks in cell culture, are currently the closest cellular models with a relevant functional endpoint to model human neuronal circuitry in a dish. Here we further developed this useful assay towards scalable drug discovery applications. We show the importance of defined neuron-to-astrocyte ratios for optimal cellular distribution and surface adherence in HTS-compatible cell culture vessels and how the cell type ratios affect network firing patterns. Increasing the neuron density resulted in decreased network spike frequencies, but increased network spike amplitudes. We identified DAPT, a molecule previously shown to promote neuronal maturation and synapse formation, as a negative regulator of astrocyte viability. Furthermore, inclusion of GABAergic neurons in the cocultures increased the network spike frequency while reducing network spike amplitudes. The GABAA receptor antagonist bicuculline did not affect network spike frequency, but increased network spike amplitudes. In order to access local field activity in an automated and scalable calcium imaging environment, we developed a pixel-based analysis for plate reader data. This method revealed that the effect of GABAergic neurons and bicuculline was restricted to local field calcium activity that coincided with synchronized network spikes. Our observations are consistent with previous findings suggesting that the presence of GABAergic neurons decreases synchronization and network spike participation of local neuronal activity, thus potentially echoing aspects of GABA action in vivo, and dysregulation thereof in pathological conditions.